ZnO-based nanocrystalline powders with applications in hybrid photovoltaic cells - Damonte, Laura Cristina (2010)
In recent years there has been a growing interest in the development of hybrid photovoltaic cells consisting of new materials, such as devices based on the combination of a wide gap semiconductor and an organic dye (dye-sensitized solar cells, DSSC). In this paper we obtain nano-zinc oxide particles whose optical and electrical properties have been modified by the presence of small amounts of Al or In acting as dopants. The aim of this study is to improve the compatibility of each of the compounds present in the photovoltaic solar cell. The knowledge gained will provide input to guide the processes in the manufacture of hybrid solar cells.